Land-use change dominates amphibian biodiversity loss, with antagonistic interactions with climate change in the karst region of Guizhou, China - Jing Liu; Shize Li; Gang Wei; Tuo Shen; Lang Mu; Haijun Su (Journal of Environmental Management, 2026)

In vitro screening and probiotic evaluation of lactic acid bacteria exhibiting potential to enhance intestinal barrier function and antioxidant properties - Shishen Liu; Lu Feng; Haijun Mu; Shenhuizi Chen; Xue Han; Qian Xu (Food Bioscience, 2026)

Dihydrotestosterone binding to the androgen receptor inhibits apoptosis in ovine undifferentiated granulosa cells via AMH signaling - Yufen Zhao; Haijiang Liu; Zhe Mu; Haijun Li (Animal Reproduction Science, 2026)

Treatment of shale gas fracturing flowback fluid using a novel multistage flocculation reactor: Energy-matching mechanism and field validation - Xing Liang; Can Cui; Lulu Xu; Yumin Mu; Gang Jin; Chang Liu; Liang Li; Haijun Zhang; Xiaobing Li (Process Safety and Environmental Protection, 2026)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

Abrasion-resistant polyethersulfone/Al2O3 membranes with excellent permeability: Fabrication, evaluation, and molecular dynamics simulation - Shiyu Gao; Liuhua Mu; Haijun Yang; Binjie Zhou; Haiping Fang; Shiqi Sheng (Journal of Water Process Engineering, 2025)

Intensification of flocculation efficiency in multi-stage reactors by optimizing the multi-cone segment configuration - Xing Liang; Mian Wu; Xuzhou Yang; Yumin Mu; Can Cui; Liang Li; Haijun Zhang; Xiaobing Li (Journal of Environmental Chemical Engineering, 2024)

Cytotoxic, clonal fidelity, and antioxidant evaluation of in vitro propagated Vitex negundo var. cannabifolia - Xue Meng; Fangfang Mu; Zeyu Zhang; Xinru Wu; Tiantian Gao; Fenglan Zhao; Jianping Xue; Yongbo Duan; Haijun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)